REKONSTRUKSI PELAPORAN KEUANGAN MASJID YANG DISESUAIKAN DENGAN SAK SEBAGAI WUJUD KELUASAN PERTANGGUNGJAWABAN (Studi Kasus pada Masjid Agung Baitul Mukminin Jombang) - Fitri Ahmad Kurniawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2022)
This research aims to know and understand the process of reconstructing the mosque's financial statements in accordance with Financial Accounting Standards. Theory in this research is to use the Legitimacy Theory. This study uses a descriptive qualitative approach. The object of this research is the Great Mosque of Baitul Mukminin Jombang. The data analysis technique used to pattern matching techniques. The results showed that the reconstruction of the mosque's financial reporting preparation is made based on the accounting cycle, starting with the identification of transactions or accounts, then journalizing (general journal) to become financial statements in accordance with applicable accounting standards, taking into account the characteristics of the report in accordance with SAK